The impact of empirical Marshall vein ethanol infusion as a first-choice intraoperative strategy on the long-term outcomes in patients with persistent atrial fibrillation undergoing mitral isthmus ablation - Du, Xianfeng; Luo, Chenxu; Shen, Caijie; Xu, Yao; Feng, Mingjun; Jin, He; Fu, Guohua; Wang, Binhao; Liu, Jin; Gao, Fang; Chu, Huimin (Frontiers in Cardiovascular Medicine, 2023)
Background: Marshall vein ethanol infusion (MVEI) as an additional therapy to conventional catheter ablation (CA) has been proved to be efficacious in patients with persistent atrial fibrillation (PeAF). However, whether empirical MVEI could be the first-line strategy in mitral isthmus (MI) ablation has seldomly been investigated. We aim to compare the efficacy, safety and long-term outcomes between provisional and empirical MVEI in PeAF patients undergoing their index MI ablation.We enrolled 133 patients with PeAF either into the provisional group (n=38, MVEI was performed when conventional endocardial and/or epicardial ablations were inadequate to achieve bidirectional MI block) or the empirical group (n=95, MVEI was applied empirically before MI CA).Results: All of the baseline characteristics were comparable. Less spontaneous or inducible atrial tachycardias (ATs) were encountered in the empirical group (P<0.001). More epicardial ablations were applied (26.3% vs 9.5%, P=0.016) and higher incidence of CA-facilitated restoration of sinus rhythm was recorded (86.8% vs 11.7%, P<0.001) in the provisional group. Although more fluoroscopy time (6.4[4.2, 9.3] vs 9.5[5.9, 11.6] min, P=0.019) and radiation exposure (69.0[25.3, 160.2] vs 122.0[62.5, 234.1] mGy, P=0.010) were documented in the empirical group with comparable procedure time, less time (455.9±192.2 vs 366.5±161.3 sec, P=0.038) was consumed to achieve bidirectional MI block during endocardial ablation in the empirical group. Incidences of procedure-related complications were similar between groups. During a 16.5±4.4-month follow-up, the empirical group showed significantly higher freedom from AT recurrence (95.8% vs 81.6%, logrank P=0.003), while the freedoms from AF or atrial tachyarrhythmias (combining AF and AT) recurrences were similar. Both univariate (HR 0.19, 95%CI 0.05-0.64, P=0.008) and multivariate (HR 0.25, 95%CI 0.07-0.92, P=0.037) Cox regression analyses indicated that empirical MVEI was independently associated with lower long-term AT recurrence.Among patients with PeAF underwent their index MI ablations, empirical MVEI could reduce the endocardial MI ablation time and improve the long-term freedom from AT recurrence.